Diabetes Complications at Presentation and One Year by Glycated Haemoglobin at Diagnosis in a Multiethnic and Diverse Socioeconomic Population: Results from the South London Diabetes Study - Mohsin Azam; Lindsey Marwood; Khalida Ismail; Tyrrell Evans; Sobha Sivaprasad; Kirsty Winkley; Stephanie Anne Amiel (Journal of Diabetes Research)
Background. WHO’s recommendation of HbA1c≥48 mmol/mol (6.5%) as diagnostic for type 2 diabetes mellitus (T2DM) was adopted by three UK London boroughs in May 2012. The South London Diabetes (SOUL-D) study has recruited people with newly diagnosed T2DM since 2008. We compared participants diagnosed before May 2012 with HbA1c<48 mmol/mol to those with diagnostic HbA1c≥48 mmol/mol. Methods. A prospective cohort study of newly diagnosed T2DM participants from 96 primary care practices, comparing demographic and biomedical variables between those with diagnostic HbA1c<48 mmol/mol or HbA1c≥48 mmol/mol at recruitment and after one year. Results. Of 1488 participants, 22.8% had diagnostic HbA1c<48 mmol/mol. They were older and more likely to be white (p<0.05). At recruitment and one year, there were no between-group differences in the prevalence of diabetic complications, except that those diagnosed with HbA1c<48 mmol/mol had more sensory neuropathy at recruitment (p=0.039) and, at one year, had new myocardial infarction (p=0.012) but less microalbuminuria (p=0.012). Conclusions. Use of HbA1c≥48 mmol/mol as the sole T2DM diagnostic criterion may miss almost a quarter of those previously diagnosed in South London yet HbA1c<48 mmol/mol may not exclude clinically important diabetes.